POLA BAKTERI PADA URIN PASIEN YANG MENGGUNAKAN KATETER URETRA DI RUANG PERAWATAN INTENSIF RSUP PROF. DR. R. D. KANDOU MANADO - Chandra, Melisa P.; Waworuntu, Olivia; Buntuan, Velma (e-Biomedik, 2014)
Abstract: Urinary catheterization as a part of invasive procedure application poses the risk of nosocomial infection to intensive care unit patients. The probability of nosocomial infection increases in accordance to the period of catheterization; longer catheterization time yields higher chances for microbial contamination on urinary catheter as catheterization provides an opening for microbial invasion into the urinary track. There are various pathogens commonly associated with catheterization including Escherichia coli, Klebsiella pneumonia, Proteus mirabili, Pseudomonas aeruginosa, Enterobacter, Staphylococcus aureus, Enterococcus fecalis, Serratia and Candida. The main objective of this research project is to observe bacterial pattern of urine from catheterized intensive care unit patients in the Prof. DR. R. D. Kandou Public Hospital Manado. A total of 20 urine samples were obtained, one sample from each individual catheter over 2 months period. Each collected sample is subsequently passed on to microbiology laboratory to undergo bacteria identification process via culture media. The preliminary results show that the identified bacterial pattern is Staphylococcus aureus, Candida, Streptococcus, Diplococcus, Proteus vulgaris, Lactobacillus, Bacillus subtilis, Enterobacter aglomerans, Citrobacter freundii dan Shigella. Following an in-depth multi-dimensional analysis of preliminary research results, the conclusion can be drawn that the most commonly found bacteria is Staphylococcus aureus. This study is part of growing body of microbiology research in catheter-related bacterial pattern and nosocomial infection; this research project will contribute to future research on similar topics. Keywords: bacteria, bacterial pattern, urinary catheter, nosocomial infection, intensive care unit.     Abstrak: Kateterisasi urin adalah bagian dari penggunaan prosedur invasif  membawa resiko infeksi nosokomial bagi pasien yang dirawat di ruang perawatan intensif.  Semakin lama kateter terpasang maka peluang kateter terkontaminasi oleh mikroba semakin besar, karena penggunaan kateter memungkinakan  jalur masuk mikroba ke dalam saluran kemih.Terdapat berbagai macam  patogen yang menyebabkan ISK yang diasosiasikan dengan kateterisasi termasuk Escherichia coli, Klebsiella pneumoniae, Proteus mirabilis, Pseudomonas aeruginosa, Enterobacter, Staphylococcus aureus, Enterococcus fecalis, Serratia, Candida. Tujuan dari penelitian ini adalah untuk mengetahui pola bakteri pada urin pasien yang menggunakan kateter uretra di ruang perawatan intensif RSUP. Prof. Dr. R. D. Kandou Manado sebanyak 20 sampel. Sampel di ambil dari urin kateter pasien yang di rawat di ruang perawatan intensif. Identifikasi bakteri dilakukan dengan menggunakan media kultur. Hasil dari kultur urin menunjukan pola bakteri yang berhasil diidentifikasi yakni Staphylococcus aureus, Candida, Streptococcus, Diplococcus, Proteus vulgaris, Lactobacillus, Bacillus subtilis, Enterobacter aglomerans, Citrobacter freundii dan Shigella. Dari hasil kesimpulan pada penelitian ini didapatkan  jenis bakteri yang paling banyak ditemukan adalah Staphylococcus aereus. Mengikuti analisis data hasil penelitian beberapa saran tentang proses penelitian lebih lanjut akan diusulkan. Kata kunci: bakteri, pola kuman, kateter uretra, infeksi nosocomial, ruang perawatan intensif.